INFLUENCE OF ENVIRONMENTAL FACTORS ON THE CONDITION OF ADOLESCENT DENTAL HARD TISSUES: CLINICAL AND PHYSICOCHEMICAL ANALYSES - Eshiev, Abdyrakman; Asanov, Azizbek; Moldaliev, Zhoomart; Eshiev, Daniyar; Arstanbekov, Mamatzhan (LPPM Universitas Jambi, 2025)
The aim of the work was to investigate the peculiarities of the influence of environmental factors on the state of the dento-mandibular system in 15-year-old adolescents. Patients were examined in a dental chair using standard sets of examination instruments: mirror, forceps, and probe. Visual assessment of the state of oral organs and tissues was carried out using standardized indices. In male subjects, the index value of the calculated microbiological activity index living in Aidarken, Sumsar and Shakaftar were significantly worse compared to controls. The concentration of different minerals in saliva in this group was 1.5E-07±2E-08, which is an essential indicator to assess the mineral balance and remineralization potential of tooth enamel. The value of the lesion index ratio in this group was 4.211±0.397, which is a statistically significant deviation (p<0.005). This increase can be explained by the chemical influence on the population due to the activity of plastic factories, which negatively affects the oral health of adolescents and increases the risk of caries development. This result emphasizes the importance of considering environmental factors when assessing dental health in different regions. Importantly, significant differences were found between groups depending on the dominant unfavourable factor. This means that different environmental and chemical factors may have different effects on the caries-forming activity of dental plaque, which requires an individualized approach to caries prevention and treatment in different settings.